What to consider when pseudohypoparathyroidism is ruled out: iPPSD and differential diagnosis - Arrate Pereda; Intza Garin; Spanish Network for Imprinting Disorders; Guiomar Perez de Nanclares (BMC, 2018)
Abstract Background Pseudohypoparathyroidism (PHP) is a rare disease whose phenotypic features are rather difficult to identify in some cases. Thus, although these patients may present with the Albright's hereditary osteodystrophy (AHO) phenotype, which is characterized by small stature, obesity with a rounded face, subcutaneous ossifications, mental retardation and brachydactyly, its manifestations are somewhat variable. Indeed, some of them present with a complete phenotype, whereas others show only subtle manifestations. In addition, the features of the AHO phenotype are not specific to it and a similar phenotype is also commonly observed in other syndromes. Brachydactyly type E (BDE) is the most specific and objective feature of the AHO phenotype, and several genes have been associated with syndromic BDE in the past few years. Moreover, these syndromes have a skeletal and endocrinological phenotype that overlaps with AHO/PHP. In light of the above, we have developed an algorithm to aid in genetic testing of patients with clinical features of AHO but with no causative molecular defect at the GNAS locus. Starting with the feature of brachydactyly, this algorithm allows the differential diagnosis to be broadened and, with the addition of other clinical features, can guide genetic testing. Methods We reviewed our series of patients (n = 23) with a clinical diagnosis of AHO and with brachydactyly type E or similar pattern, who were negative for GNAS anomalies, and classify them according to the diagnosis algorithm to finally propose and analyse the most probable gene(s) in each case. Results A review of the clinical data for our series of patients, and subsequent analysis of the candidate gene(s), allowed detection of the underlying molecular defect in 12 out of 23 patients: five patients harboured a mutation in PRKAR1A, one in PDE4D, four in TRPS1 and two in PTHLH. Conclusions This study confirmed that the screening of other genes implicated in syndromes with BDE and AHO or a similar phenotype is very helpful for establishing a correct genetic diagnosis for those patients who have been misdiagnosed with "AHO-like phenotype" with an unknown genetic cause, and also for better describing the characteristic and differential features of these less common syndromes.